Hubungan Kontrol Diri dengan Media Sosial Guna Membangun Personal Branding pada Siswa - Muhammad Rofai Simorangkir; Ulfa Danni Rosada (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
This research aims to determine the relationship between self-control and social media in order to build personal branding in class XI students at SMK Muhammadiyah Gamping. The method in this research is correlated with quantitative research. The population in this study was 66 class XI students. Data collection instruments use scales, namely, self-control scale, personal branding scale and social media scale. The data analysis technique used is multiple correlation analysis. Based on the results of data processing, it is known that the sig value of the self-control, social media and personal branding variables is 0.402. These results show that the three variables have a sig value > 0.05, which means the data is normally distributed so it can be concluded that high self-control can be a reference for managing, controlling and leading to a positive direction in using social media so that students' personal branding abilities increase. Novelty in this research can be seen if students have high self-control and use social media wisely, then students' personal branding will increase.